1981
DOI: 10.1002/j.1552-4604.1981.tb01753.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pindolol on Blood Pressure, Plasma Renin Activity, and Catecholamines in Hypertensive Patients

Abstract: The effects of 45 mg pindolol daily on blood pressure, heart rate, plasma renin activity, and plasma catecholamines were assessed on 11 hospitalized hypertensive patients. Blood pressure decreased significantly after nine days of treatment, but heart rate remained unchanged. Plasma renin activity was in the same average range before and during treatment, with individual values variably increasing, decreasing, or remaining unchanged. Blood pressure changes were independent from the baseline level of plasma reni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
1984
1984

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Accordingly the rise in plasma noradrenaline in no way excludes an effect of prejunctional Padrenoceptor blockade. Furthermore, it has been shown that during treatment with pindolol plasma noradrenaline does decrease (Walter et al, 1973;Anavekar et al, 1975;Brecht et al, 1976aBrecht et al, , 1976bLang et al, 1978;Winer et al, 1978;Franz et al, 1980, Gavras et al, 1981Kirsten et al, 1982;Wilcox et al, 1981), (Table 2). It has also been shown that in the course of treatment with practolol, the urinary excretion of catecholamines is reduced by 65 % (Esler & Nestel, 1973).…”
Section: Prejunctional8-adrenoceptor Theorymentioning
confidence: 98%
“…Accordingly the rise in plasma noradrenaline in no way excludes an effect of prejunctional Padrenoceptor blockade. Furthermore, it has been shown that during treatment with pindolol plasma noradrenaline does decrease (Walter et al, 1973;Anavekar et al, 1975;Brecht et al, 1976aBrecht et al, , 1976bLang et al, 1978;Winer et al, 1978;Franz et al, 1980, Gavras et al, 1981Kirsten et al, 1982;Wilcox et al, 1981), (Table 2). It has also been shown that in the course of treatment with practolol, the urinary excretion of catecholamines is reduced by 65 % (Esler & Nestel, 1973).…”
Section: Prejunctional8-adrenoceptor Theorymentioning
confidence: 98%